Phase I trial of intranasal NEO100, highly purified perillyl alcohol, in adult patients with recurrent glioblastoma. Issue 1 (12th February 2021) - Schönthal, Axel H; Peereboom, David M; Wagle, Naveed; Lai, Rose; Mathew, Anna J; Hurth, Kyle M; Simmon, Vincent F; Howard, Steven P; Taylor, Lynne P; Chow, Frances; da Fonseca, Clovis O; Chen, Thomas C
Abstract: Background: Better treatments for glioblastoma (GBM) patients, in particular in the recurrent setting, are urgently needed. Clinical trials performed in Brazil indicated that intranasal delivery of perillyl alcohol (POH) might be effective in this patient group. NEO100, a highly purified version of POH, was current good manufacturing practice (cGMP) manufactured to evaluate the safety and efficacy of this novel approach in a Phase I/IIa clinical trial in the United States. Methods: A total of 12 patients with recurrent GBM were enrolled into Phase I of this trial. NEO100 was administered by intranasal delivery using a nebulizer and nasal mask. Dosing was 4 times a day, every day. Four cohorts of 3 patients received the following dosages: 96 mg/dose (384 mg/day), 144 mg/dose (576 mg/day), 192 mg/dose (768 mg/day), and 288 mg/dose (1152 mg/day). Completion of 28 days of treatment was recorded as 1 cycle. Adverse events were documented, and radiographic response via Response Assessment in Neuro-Oncology (RANO) criteria was evaluated every 2 months. Progression-free and overall survival were determined after 6 and 12 months, respectively (progression-free survival-6 [PFS-6], overall survival-12 [OS-12]). Results: Intranasal NEO100 was well tolerated at all dose levels and no severe adverse events were reported. PFS-6 was 33%, OS-12 was 55%, and median OS was 15 months. Four patients (33%), all of them with isocitrate dehydrogenase 1 (IDH1)-mutant tumors, survived >24 months. Conclusion: Intranasal glioma therapy with NEO100 was well tolerated. It correlated with improved survival when compared to historical controls, pointing to the possibility that this novel intranasal approach could become useful for the treatment of recurrent GBM.